Human Development Index and Its Enhancement with Selection Procedure of Its Components - Banjade, Ishwari Prasad; Gautam, Shanta (Journal of Advanced College of Engineering and Management, 2022)
This paper aims to identify the rational components and statistical technique to measure of performance in key dimensions of human development. The study uses desk review particularly the literature that focused quantitative techniques and human development. Different ideas, models, concepts and knowledge of human development are drawn from various literature. Those models and concepts of human development are evolving over time and building on the strengths and weaknesses of the previous models and concepts. Many recent studies suggest that the Human Development Index (HDI) is incomplete and so there is an urgent need to modify and develop new measuring tool for human development. In connection with this issue the study focuses to identify and develop rational components and appropriate model that can overcome the deficiency of the existing models. The study recommends to use Principal Component Analysis (PCA) and Multiple Regression Analysis (MRA)which are found statistical techniques to develop the estimators for measuring the level of human development. The appropriate components and modified models are proposed on the basis of derived components with statistical techniques for measuring the level human development in rational manner.